Double-balloon enteroscopy in children – a tertiary care experience. (4th April 2011) - Urs, A N; Rao, P C; Arian, Z; Thomson, M
Abstract : Background: Double-balloon enteroscopy (DBE) has become a preferred method for management of small bowel disorders in adult population. Experience in paediatric population remains limited and we present our experience with the use of DBE. Methods: 34 procedures were performed on 33 patients (22M;11F) from January 2004 to October 2010, with median age of 12.9 years (range 2–18) and median weight of 39.8 kg (range 15.5–95); nine for Peutz-Jeghers syndrome (PJ syndrome), seven for obscure gastrointestinal (GI) bleeding, five with angiomatous malformations having persistent GI bleeding, five with Crohn's disease, three for chronic abdominal pain, and two with Cowden's syndrome with multiple polyps, one for lymphangiectasia, pseudo-obstruction and jejunal stenosis. Results: The entire small bowel was examined in 11 patients and a length between 150 cm and 400 cm distal to pylorus in the remaining 23. 21 patients had both antegrade (trans-oral) and retrograde (trans-anal and via ileostomy in two cases) examinations. The median examination time was 118 min (range 50–320). No complications were encountered. Polyps were detected and successfully removed in all nine patients with PJ syndrome, in a patient with tubulo-villous adenoma of the distal duodenum, in three patients with significant anaemia, and in two patients with Cowden's syndrome. The source of bleeding was identified in a further patient with oesophageal varices. Diagnosis of Crohn's disease was confirmed in two suspected patients. Three patients, known for Crohn's underwent DBE, to examine the extent of disease. One patient with feed intolerance found to have severe dysmotility. A diagnosis was made in a patient with multiple angiomata not amenable to endotherapy, and in three, with a discrete angioma which were treated with argon plasma coagulation. One patient with protein-losing enteropathy was diagnosed to have isolated intestinal lymphangiectasia. One patient with GI bleed had large ulcer at ileocolonic anastomosis site. DBE was normal or revealed minor mucosal friability in the remaining six patients. A diagnostic yield of 28/34(82%) with therapeutic success in 17/34 (50%) was achieved. Conclusion: DBE appears to be a safe diagnostic and therapeutic tool with suspected small bowel disorders. Further larger studies are required to establish widespread application.